2008
DOI: 10.1200/jco.2007.13.4403
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results From a Randomized Phase II Trial of Standard- Versus Higher-Dose Imatinib Mesylate for Patients With Unresectable or Metastatic Gastrointestinal Stromal Tumors Expressing KIT

Abstract: Nearly 50% of patients with advanced GIST who were treated with imatinib mesylate survived for more than 5 years, regardless of a 400 or 600 mg/d starting dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
675
7
15

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 937 publications
(747 citation statements)
references
References 18 publications
26
675
7
15
Order By: Relevance
“…The response rate (68.4%) in the present study was similar to that previously reported [8,28]. The response rate was 54% in the initial report of the B2222 study, but it increased to 66.7% with long-term follow-up.…”
Section: Discussionsupporting
confidence: 80%
“…The response rate (68.4%) in the present study was similar to that previously reported [8,28]. The response rate was 54% in the initial report of the B2222 study, but it increased to 66.7% with long-term follow-up.…”
Section: Discussionsupporting
confidence: 80%
“…Treatment with IM produces an objective response or stable disease in >80% of patients with metastatic and/or unresectable GIST. However, the success of IM in these patients is tempered by the reality that treatment increases the median time to tumor progression by just two years (2-4). Second and third-line therapies, sunitinib and regorafenib, provide additional disease stabilization measured in months (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…4 The median time to disease progression is about 18 or 20 months when treated at 400 or 800 mg dose levels. 5,6 Therefore, the best treatment regimen for patients with malignant GISTs, like doing imatinib preoperatively or postoperatively, is still under debate. [7][8][9] The guideline for the selection of patients for adjuvant therapy varies among experts, mainly due to the criteria predicting patients with a high risk of recurrence after the surgical removal of primary GISTs have yet to be established.…”
mentioning
confidence: 99%